Evaluation of Bioactive Compounds, Release Profiles, and Toxicity Test from Microcapsules Containing R. tuberosa L. Extracts Utilizing Gum Arabic - Almayda, Nabila; Roosdiana, Anna; MASRURI, Masruri; Safitri, Anna (The Journal of Pure and Applied Chemistry Research, 2024)
This study is essential to analyze the toxicity and release of bioactive compounds in R. tuberosa L. extract microcapsules coated with gum Arabic and to provide information on the use of microcapsules as a drug delivery system with controlled release of active ingredients. Investigations focused on the effect of pH and timing on discharge kinetics, as well as toxicity evaluation. The release of active ingredients from microcapsules was carried out in medium variations, namely pH 2.2 and pH 7.4, with release durations of 30, 60-, 90-, 120-, and 150-min. Bioactive compounds were released by 59.23% at pH 2.2 and 58.21% at pH 7.4 within 150 min. The BSLT (brine shrimp lethal toxicity) assay was used using brine shrimp larvae (Artemia salina L.), resulting in a non-toxic classification as evidenced by an LC50 value of 5729 Î¼g/mL. Microcapsules in optimum conditions were then characterized using FTIR (Fourier-Transform Infrared) and SEM (scanning electron microscopy) instruments. The FTIR analysis showed variations in functional groups in R. tuberosa L. extracts, gum Arabic, and microcapsules. Furthermore, the SEM examination highlighted the morphology of microcapsules that were mostly spherical.